ANALISA GETARAN UNTUK MENGETAHUI TINGKAT KERUSAKAN BEARING MESIN GERINDA DUDUK - Syahrul, Mochammad; Margianto, Margianto; Lesmanah, Unung (UNIVERSITAS ISLAM MALANG, 2013)
Maintenance management that most widely used in large companies are predictive maintenance. Predictive maintenance that most dominant in the machine vibration analysis is to detect bearing defect of the engine. However, vibration analysis is often dominated by an engineer to measure the vibration characteristics in the time domain and frequency domain which occurs in the radial direction. Simplification method by looking at the value of displacement, velocity, and acceleration between the bearing vibration standards with reduced bearing clearance will be able to facilitate all the mechanics to determine the level of bearing defect. Reducing bearing clearance at the time of testing is done by reducing the diameter of the bearing of 0.05 mm, 0.1 mm, 0.15 mm, and 0.2 mm with turner machine. Then measured vibration at each bearing left and right of each of these variables. The results of these tests can generally be concluded that there is no relationship between bearing clearance with displacement bearing vibration, and there is a significan relationship between bearing clearance with the speed and acceleration of vibration that can be used as a reference to determine the level of the bearing defect. The higher value of vibration velocity and acceleration, then the level of bearing damage will higher.